2016
DOI: 10.4236/ajps.2016.71020
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Aspects of Grape (<i>Vitis vinifera</i> L.) Clusters Afflicted with SOUR Shrivel Is Related to Functionality of Its Vascular Tissues

Abstract: Mineral nutrition is essential to growth and development of various plant organs including fruits; consequently deficiency of any element leads to a myriad of physiological disorders, which in fruits are manifested as ripening anomalies. In this study, nutritional composition in tandem with vascular structure of healthy grape clusters and clusters afflicted with SOUR shrivel, a ripening disorder has been examined to unravel its mechanistic basis. The healthy berries without any affliction accumulated the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Besides the biochemistry related processes during ripening, a possible additional explanation of lower sugar accumulation could be a disturbed translocation of assimilates within the vascular system of affected grape clusters. Previous studies showed reduced cell viability in the rachis of BS grapes possibly leading to a reduced transport function, although obvious necrosis on the outside of the rachis is not observed in our case (Hall et al 2011 ; Bondada 2016 ). Recently, in-depth microscopic study of symptomatic BS Zweigelt grapes showed cell deformations and signs of total or more likely partial occlusion of the phloem sieve elements (Crespo-Martínez et al 2019 ).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Besides the biochemistry related processes during ripening, a possible additional explanation of lower sugar accumulation could be a disturbed translocation of assimilates within the vascular system of affected grape clusters. Previous studies showed reduced cell viability in the rachis of BS grapes possibly leading to a reduced transport function, although obvious necrosis on the outside of the rachis is not observed in our case (Hall et al 2011 ; Bondada 2016 ). Recently, in-depth microscopic study of symptomatic BS Zweigelt grapes showed cell deformations and signs of total or more likely partial occlusion of the phloem sieve elements (Crespo-Martínez et al 2019 ).…”
Section: Discussioncontrasting
confidence: 65%
“…Past studies focused on morpho-anatomical issues (Hall et al 2011 ; Bondada and Keller 2012a ; Bondada 2014 ; Crespo-Martínez et al 2019 ), nutritional aspects (Bachteler et al 2015 ; Bondada 2016 ; Griesser et al 2017 ), viticultural practices (Raifer et al 2014 ) or on a restricted list of genes (Griesser et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cell death was more often observed in the rachis cortex and epidermis than in the phloem, and there was typically more cell death in the berries than in the rachis. So, while there may be a relationship between cell death in the rachis and development of BS symptoms (Hall et al 2011, Zufferey et al 2015, Bondada 2016, Crespo‐Martínez et al 2019), the former does not necessarily cause the latter. The present study, however, and earlier research (Krasnow et al 2008, 2009, Tilbrook and Tyerman 2008, Singh 2010, Bondada and Keller 2012a,b) consistently found that berries from BS‐affected bunches of wine and tablegrapes had lower mesocarp cell viability than berries from normally developing bunches.…”
Section: Discussionmentioning
confidence: 99%
“…Much research aimed at furthering our understanding of BS has focused on the microscopic examination of berries or vascular tissues in the rachis. Partial cell death and other anomalies have been detected in both the berry mesocarp (Krasnow et al 2008, 2009, Bondada and Keller 2012a, 2012b, Bondada 2014) and the rachis phloem (Hall et al 2011, Zufferey et al 2015, Bondada 2016, Crespo‐Martínez et al 2019) of bunches with BS symptoms. More recently, gene expression has been analysed to identify early changes leading to BS symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Dissimilar from bunch stem necrosis, rachis and pedicels stay viable and green with no obvious symptoms on the surface. Nevertheless morpho-anatomical study observed cell death in the rachis of symptomatic grape clusters of Cabernet Sauvignon (Bondada and Keller 2012b;Hall et al 2011), TEM analysis showed collapsed cells and cell wall thickenings in the secondary phloem (Crespo-Martinez et al 2019) and light microscopy and SEM analyses revealed higher rates of callose deposition on sieve plates (Bondada 2016;Crespo-Martinez et al 2019). Reduced cell viability was also observed in grape berries leading to the assumption that the loss of cell membrane integrity is an important factor for water loss and berry shrinkage (Krasnow et al 2008(Krasnow et al , 2012.…”
Section: Introductionmentioning
confidence: 99%